Speech Act Analysis On Facebook Statuses Used By Students Of Muhammadiyah University Of Surakarta - Wulandari, Susi; , Dra. Malikatul Laila, M. Hum; , Dr. Dwi Haryanti, M.Hum (2014)
The present research aims at identifying the types of speech act and describing the functions of each type of the speech act on facebook statuses used by students of Muhammadiyah University of Surakarta. The type of this research is descriptive qualitative research in which the writer uses documentation and observation method as the method of collecting data. The data of this research are written utterances made by students of class A of English Department in Muhammadiyah University of Surakarta. The data sources are from facebook, having the shape of facebook statuses. The results of the research show that firstly based on the types of speech act. From 160 data the researcher finds five types of speech act. There are 53 data or 33, 13% which are representatives act, 34 data or 21, 25%, directives act, 8 data or 5, 00%, commissives act, 64 data or 40, 00%, expressives act, and 1 datum or 0, 62%, declarations act. The second result is the functions of each type of the speech act. There are 30 functions of the speech act on facebook statuses. (1) Representative act having functions describing, asserting, and informing; (2) Directives act having functions requesting, commanding, persuading, prohibiting, asking, and suggesting; (3) Commissives act having functions offering and promising; (4) Expressives act having functions to show sorrow feeling, pleasure, congratulation, greeting, longing, apology, boring, confusing, disappointing, dislike, hoping, satisfying, scaring, supporting, thanking, tiredness, yearning, and anger; (5) Declarations act having function declaring.